Pijat Oksitosin sebagai Upaya Meningkatkan Produksi ASI - Fitriyah; Masruroh (Universitas Ngudi Waluyo, 2024)
The problem of lack of breast milk production in postpartum mothers is still very common. This occurs due to several factors, including the lack of knowledge of postpartum mothers about the existence of oxytocin massage and the implementation of education or counseling about oxytocin massage which is still rarely carried out. This service is carried out to carry out oxytocin massage activities for postpartum mothers and evaluate knowledge of oxytocin massage for postpartum mothers. Method: Delivery of material is carried out through lectures and discussions. The target of this counseling is postpartum mothers, where this method involves participants directly in the learning process to discuss and convey initial knowledge. The process of delivering material uses tools or media which aims to make it easier for participants to understand the material being presented. The media used are leaflets and PPT (PowerPoint). The material used is in Indonesian so that it is easier for the participants to understand. Then they directly practice Oxytocin massage to one of the postpartum mothers. This counseling was carried out on Friday 08 November 2024 at PMB Fitriyah. The implementation of activities is carried out in three stages, namely problems, solutions and evaluation. It can be concluded that based on the results of the pretest and posttest, the results showed that there was an increase in postpartum mothers' knowledge about oxytocin massage to overcome breast milk problems and increase breast milk production after being given health education or health counseling. Abstrak Permasalahan dari kurangnya produksi ASI pada ibu postpartum masih sangat sering ditemukan. Hal ini terjadi karena beberapa factor diantaranya, kurangnya pengetahuan ibu postpartum tentang adanya pijat oksitosin dan pelaksanaan edukasi atau penyuluhan tentang pijat oksitosin yang masih jarang dilakukan. Pengabdian ini dilakukan untuk melaksanakan kegiatan pijat oksitosin pada ibu postpartum dan melakukan evaluasi pengetahuan pijat oksitosin pada ibu postpartum. Metode Penyampaian materi dilakukan dengan ceramah dan diskusi, sasaran pada penyuluhan ini yaitu ibu postpartum dimana metode ini melibatkan peserta langsung dalam proses pembelajaran untuk berdiskusikan dan penyampaian pengetahuan awal. Proses penyampaian materi menggunakan alat bantu atau media yang bertujuan untuk mempermudah peserta memahami materi yang disampaikan, Media yang digunakan berupa Leaflet dan PPT (PowerPoint). Materi yang digunakan menggunakan Bahasa Indonesia agar lebih mudah dipahami oleh peserta, Kemudian mempraktekan secara langsung cara pijat Oksitosin ke salah satu ibu postpartum. Pelaksanaan penyuluhan ini dilakukan pada hari Jumat 08 November 2024 di PMB Fitriyah. Pelaksanaan kegiatan dilaksanakan dalam tiga tahap yaitu permasalahan, solusi dan evaluasi. Dapat disimpulkan Berdasarkan hasil pretest dan posttest menunjukkan hasil bahwa terjadi peningkatan pengetahuan ibu postpartum tentang pijat oksitosin untuk mengatasi permasalahan ASI dan meningkatkan produksi ASI sesudah diberikan pendidikan kesehatan atau penyuluhan kesehatan.